2024
DOI: 10.1111/jhn.13273
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of nutritional care in children and young people with acute lymphoblastic leukaemia: a narrative review

Amy L. Lovell,
Breeana Gardiner,
Louise Henry
et al.

Abstract: BackgroundAcute lymphoblastic leukaemia (ALL) is the most common paediatric malignancy in the world. Advances in treatment protocols have resulted in survival rates of >80% in most high‐income countries (HIC); however, children and young people (CYP) with ALL continue to face significant nutrition‐related challenges during treatment.MethodsThis narrative review outlines the changing landscape of treatment and survivorship for CYP with ALL and the advances in nutrition knowledge that call for changes to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 223 publications
0
1
0
Order By: Relevance
“…We recommend that dieticians work closely with families to ensure that children's caloric needs are met while also supporting adequate diet quality to attenuate excessive weight gain during treatment. 33 Caregivers reported that a decrease in physical activity was due to several factors; however, one potentially modifiable factor was pain. Indeed, pain is often endorsed by youth with ALL during active treatment and after treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that dieticians work closely with families to ensure that children's caloric needs are met while also supporting adequate diet quality to attenuate excessive weight gain during treatment. 33 Caregivers reported that a decrease in physical activity was due to several factors; however, one potentially modifiable factor was pain. Indeed, pain is often endorsed by youth with ALL during active treatment and after treatment completion.…”
Section: Discussionmentioning
confidence: 99%